Opportunities for strengthening sexual health education in schools: Findings from a student needs assessment in NSW. (9th July 2021) - Roth, Caecilia; Cheng, Yan; Wilson, Eleanor G.; Botfield, Jessica; Stuart, Anne; Estoesta, Jane
Abstract: Issue addressed: Comprehensive sexuality education (CSE) is important for the sexual and reproductive health of young people. To better understand young people's views and experiences of sexual health education in NSW, a student needs assessment survey was conducted in 2017. Methods: This paper presents the findings from 1603 NSW students in Years 8‐12 following online recruitment. Descriptive analyses explored students' views and experiences in relation to sources of sexual health information, education providers, school‐based topics covered and resources drawn on. Results: Findings indicate that school, parents, friends and social media are students' most common sources of information on sexual and reproductive health. Approximately one‐third of students reported wanting more information on topics related to relationships, reproductive health, consent and sexual decision‐making and sexual harassment, abuse and bullying, and two‐thirds of transgender and gender diverse students wanted more information on gender identity. For the topics which students reported receiving the least information about at school, they were most likely to seek this out on social media and websites. Conclusion: Findings provide valuable insight for improving CSE in NSW. The influence of social media, parents and the internet should be taken into consideration when developing resources and programme content. Professional development for educators could contribute to improving the quality of CSE delivered. Accurate and up to date resources must be utilised to support student engagement and effective learning.